Association Between D-Dimer Level with Clinical Severity and Radiological Imaging of Confirmed COVID-19 Patients at RSUP Dr. M. Djamil Padang - Hafis Herdiman; Masrul Basyar; Oea Khairsyaf (Jurnal Respirologi Indonesia, 2022)
Background: D-dimer could be used as a biomarker to distinguish the severity of COVID-19. High D-Dimer levels are associated with increased clinical severity and poor radiological imaging. This study aims to identify the correlation between D-dimer levels with clinical severity and radiological features of confirmed COVID-19 patients at RSUP dr. M. Djamil Padang.Methods: This was a cross sectional study of 202 COVID-19 confirmed patients at RSUP dr. M. Djamil Padang using medical record data from 1 January to 31 March 2021. The data were collected using convenience sampling technique and analyzed by Kruskal Wallis Test to determine the association between D-dimer levels with clinical severity and radiological features.Results: Majority of patients were in age groups of below 50 and 50-59 years, with equal proportion between men and women, and were in moderate clinical severity (58,4%). Most radiological imaging was in severe degree of 91 patients (45%). The association between D-dimer levels and clinical degree of COVID-19 patients as well as the association between D-dimer levels and severity of radiological imaging of COVID-19 patients were statistically significant (P=0.0001).Conclusion: Elevated D-dimer level was a common feature at COVID-19 confirmed patients. High levels of D-dimer were associated with increased clinical severity and severe radiological features in COVID-19 patients.